The Special Issue on Neonatology for the 10th Anniversary of Children: From Preclinical Findings to Bringing Families to the Centre of Contemporary Neonatal Care - Karel Allegaert (Children)
Neonatology is a specialized branch of medicine, focussed on the care of newborns, either related to preterm birth or other medical conditions like sepsis, asphyxia, or congenital malformations [...]